2022
DOI: 10.1016/j.scitotenv.2021.151273
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of exposure to fecal contamination in urban environment across nine cities in low-income and lower-middle-income countries and a city in the United States

Abstract: Background During 2014 to 2019, the SaniPath Exposure Assessment Tool, a standardized set of methods to evaluate risk of exposure to fecal contamination in the urban environment through multiple exposure pathways, was deployed in 45 neighborhoods in ten cities, including Accra and Kumasi, Ghana; Vellore, India; Maputo, Mozambique; Siem Reap, Cambodia; Atlanta, United States; Dhaka, Bangladesh; Lusaka, Zambia; Kampala, Uganda; Dakar, Senegal. Objective Assess and compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“… 57 This is particularly important in rural areas where both agriculture and ground-water sources remain heavily polluted with fecal contamination. 59 , 60 Additionally, factors such as healthcare coverage and household assets, such as refrigeration and clean cooking fuel, are all associated with improved child growth. 44 , 46 , 49 , 61 Poor maternal nutrition, inadequate dietary diversity, and intrastate inequality are also associated with poor child linear growth.…”
Section: Discussionmentioning
confidence: 99%
“… 57 This is particularly important in rural areas where both agriculture and ground-water sources remain heavily polluted with fecal contamination. 59 , 60 Additionally, factors such as healthcare coverage and household assets, such as refrigeration and clean cooking fuel, are all associated with improved child growth. 44 , 46 , 49 , 61 Poor maternal nutrition, inadequate dietary diversity, and intrastate inequality are also associated with poor child linear growth.…”
Section: Discussionmentioning
confidence: 99%
“…Other transmission pathways beyond those affected by WASH interventions should be considered. A recent study found that food pathways were the most common dominant route of exposure to fecal contamination across cities in LMICs . While other pathways were found to be dominant in some site-specific regions, they were often limited to smaller geographical areas .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that food pathways were the most common dominant route of exposure to fecal contamination across cities in LMICs. 71 While other pathways were found to be dominant in some site-specific regions, they were often limited to smaller geographical areas. 71 Our findings highlight, as MapSan found, that urban sanitation may not deliver the expected benefits in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…According to the study, the probability of NoV infection from oyster consumption in the US and Canada was 0.108 and 0.188, which is similar to our results [ 43 ]. Owusu et al investigated the annual probability of NoV infection in wastewater-irrigated vegetables and showed that the probability of infection ranged from 9.2 × 10 −1 to 9.4 × 10 −1 for all genotypes of NoV [ 49 ]. Ankita Bhatt et al found that the probability of infection for AdV and NoV both reached 0.9 [ 50 ].…”
Section: Discussionmentioning
confidence: 99%